Elektryczny Analog do Rozwiązywania Układów Równań Algebraicznych Pierwszego Stopnia Tworzących Macierz Normalną - Lisowski, A. (Engineering Transactions, 1970)
The phenomenon of electromechanical analogue has been used for problems of mechanics. In particular may be modelled, in an electric net, equations of the method of deformation used for beams, frames and plates. In this paper the author presents a system of an electric net which makes it possible to model an arbitrary set of algebraic linear equations provided that the coefficients of unknowns are a normal matrix – i.e., symmetrical in relation to the main diagonal – and the iterating series are convergent.